FEATURES OF A SERIES OF STUDIES ON THE ASSESSMENT OF THE SEVERITY OF ANEMIA IN CHILDREN LIVING AROUND THE ARAL SEA: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Iron deficiency anemia clinical manifestations appear that are explained the development of anemic hypoxia, which in turn increases the metabolic changes and trophic disorders present in the body. Updated criteria allow for early diagnosis and treatment before the development of damage to internal organs.